Management of COVID-19 in cancer patients receiving cardiotoxic anti-cancer therapy. Future recommendations for cardio-oncology - Hasan Kobat; Islam Elkonaissi; Mehmet Tevfik Dorak; Shereen Nabhani-Gebara (Oncology Reviews, 2021)
Cardiotoxicity induced by anti-cancer treatment has become a significant threat as the number of cardiotoxic anti-cancer agents is growing. Cancer patients are at an increased risk of contracting coronavirus disease 2019 (COVID-19) because of immune suppression caused by anti-cancer drugs and/or supportive treatment. Deterioration in lung functions due to COVID-19 is responsible for many cardiac events. The presence of COVID-19 and some of its treatment modalities may increase the chance of cardiotoxicity development in cancer patients receiving potentially cardiotoxic agents. This review provides evidence-based information on the cardiotoxicity risk in cancer patients clinically diagnosed with COVID-19 who are receiving potentially cardiotoxic anti-cancer agents. Proposed strategies relating to the management of this patient cohorts are also discussed.